Meeting the Chinese Challenge to the Regional Order. Issue 1 (16th January 2016) - Roy, Denny
Abstract : China has reached such a position of relative strength in the Asia‐Pacific region that anxiety about stimulating anti‐China security cooperation among other states, once a powerful moderating force over Chinese foreign policy making, appears less of a restraint for the nationalism‐indulgent Xi Jinping government. Chinese leaders believe that China's challenges to key aspects of the U.S.‐sponsored regional security order will result in increased regime and national security for China, but these challenges also threaten to unravel the order. If Washington and its partners are unwilling to accept the inevitable harm to their own interests that would accompany increased Chinese influence over regional affairs, they should demonstrate a willingness to pursue policies the Chinese would view as strategic setbacks, thereby causing the Chinese to recalculate the advisability of bullying behavior as opposed to cooperative behavior within the rules and institutions of the current regional order, an approach under which China has made spectacular gains.